(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aims to identify the level of Perfection Teachers of History at the Secondary level for Effective Teaching Skills ,and to achieve the aims of the study, the researcher prepared a questionnaire as a tool in a poi of history teachers in city of Latakia, and note card as a tool in the evaluation, each consisting of(25)skill, it was appiled to the teachers of the research sample after reliability and validity of each, the research sample consisted of (57)history teacher in the city of Latakia, research found that the history teachers of the sample may have Perfection the skill of (11)out of (25) skill, this result indicates a low level of mastery in the light on the test representative degree of workmanship (66,66)% and above, the study recommended that the practice of history teachers in all grades and skills of effective teaching in the classroom, and the need to hold training courses for them in order to brief them on recent trends in effective teaching skills.